Anne versus Heidi (circa 1900) : happy rurality, dangerous cities? - Casta, Isabelle Rachel (Ondina - Ondine, 2022)
Two amounts of almost contemporary children’s literature respond to each other on both sides of the Atlantic: both have as heroines young girls torn between a sad and unhappy urban experience, and an arrival in the heart of nature, fulfilling and invigorating (we would speak today resilience hui); however, between the Canadian Anne Shirley-Cuthbert (Anne of the Green Gables, Lucy Maud Montgomery) and the German Switzerland Adélaïde / Heidi (Heidi, Johanna Spyri), what differences! So, happy countryside, toxic cities? Nothing is simple, but these pre-World War I youthful accounts also assume that hope is possible, and that the world is open to strong souls. Keywords : friendship, Lucy Montgomery, nature, orphans, German-speaking Switzerland.